Composition and Drivers of Gut Microbial Communities in Arctic-Breeding Shorebirds - Grond, Kirsten; Santo Domingo, Jorge W.; Lanctot, Richard B.; Jumpponen, Ari; Bentzen, Rebecca L.; Boldenow, Megan L.; Brown, Stephen C.; Casler, Bruce; Cunningham, Jenny A.; Doll, Andrew C.; Freeman, Scott; Hill, Brooke L.; et al. (Frontiers in Microbiology, 2019)
Gut microbiota can have important effects on host health, but explanatory factors and pathways that determine gut microbial composition can differ among host lineages. In mammals, host phylogeny is one of the main drivers of gut microbiota, a result of vertical transfer of microbiota during birth. In birds, it is less clear what the drivers might be, but both phylogeny and environmental factors may play a role. We investigated host and environmental factors that underlie variation in gut microbiota composition in eight species of migratory shorebirds. We characterized bacterial communities from 375 fecal samples collected from adults of eight shorebird species captured at a network of nine breeding sites in the Arctic and Subarctic ecoregions of North America, by sequencing the V4 region of the bacterial 16S ribosomal RNA gene. Firmicutes (55.4%), Proteobacteria (13.8%), Fusobacteria (10.2%) and Bacteroidetes (8.1%) dominated the gut microbiota of adult shorebirds. Breeding location was the main driver of variation in gut microbiota of breeding shorebirds (R2 = 11.6%), followed by shorebird host species (R2 = 1.8%), and sampling year (R2 = 0.9%), but most variation remained unexplained. Site variation resulted from differences in the core bacterial taxa, whereas rare, low-abundance bacteria drove host species variation. Our study is the first to highlight the potential importance of local environment as a driver of gut microbiota composition in wild, migratory birds under natural conditions.